Surface wear-resistant molecular sieve and preparation method and application thereof
By preparing surface wear-resistant molecular sieve, the existing molecular sieve has solved the problems of poor wear resistance and serious powder loss, and achieved high wear resistance and low surface dust. It is suitable for adsorbents in refrigeration systems.
Patent Information
- Application Number
- CN202411707897.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing refrigeration system has poor anti-wear performance and serious powder loss problems, resulting in blockage of refrigeration pipelines.
A surface wear-resistant molecular sieve is prepared by a method of preparing a surface wear-resistant molecular sieve, including mixing the A-type molecular sieve raw powder, the first binder, the reinforcement and water, pre-wet the surface and applying the surface trimming powder, and then drying and calculating it after curing, forming a molecular sieve with excellent wear-resistant properties and low surface dust.
It achieves excellent wear resistance and low surface dust of molecular sieve, high static water adsorption and low wet wear, and is suitable for adsorbents in refrigeration systems.
Smart Images

Figure BDA0005154949330000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieves, and in particular to a surface wear-resistant molecular sieve and a preparation method and application thereof. Background Art
[0002] The refrigeration device is a closed circulation system, and no other impurities are allowed to be mixed into its circulating working fluid. However, whether it is the production of refrigerants or the operation of refrigeration systems, it is easy to introduce other impurities, such as water, acidic gases and mechanical impurities, which will have a huge negative impact on the refrigeration system. Among the above impurities, the impact of water is the most obvious. At present, the commonly used refrigerants are mainly fluorinated alkane refrigerants. When producing these fluorinated alkane refrigerants, it is very easy to introduce a certain amount (<10 -4 ) of water. At extremely low temperatures, this water will form solid ice to block the refrigeration pipeline; when the water content exceeds the standard, acidic impurities will be produced. When used for a long time, these acidic impurities will corrode the pipeline, causing the refrigeration system to malfunction. Therefore, a drying device must be added during the production process of fluorinated alkane refrigerants to remove trace amounts of water impurities.
[0003] Molecular sieves for refrigeration systems have good selective adsorption performance and good deep purification performance, and are widely used to remove trace water impurities in fluorinated alkane refrigerants. An ideal molecular sieve desiccant should not only have good trace water impurity deep removal capabilities, but also have properties such as not reacting with refrigerants and not affecting the use of refrigeration media. Although the existing molecular sieves for refrigeration systems on the market can meet the above performance requirements, they generally have poor wear resistance and severe powder falling problems, which can cause blockages in refrigeration pipelines. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a surface wear-resistant molecular sieve and a preparation method and application thereof. The molecular sieve prepared by the present invention has excellent wear resistance and low surface dust.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a surface wear-resistant molecular sieve, comprising the following steps:
[0007] Mixing the A-type molecular sieve raw powder, the first binder, the reinforcing agent and water to form an intermediate product to be surface-finished;
[0008] Pre-wetting the surface of the intermediate product to be surface-finished and applying surface-finishing powder on the surface in sequence, and curing to obtain a surface-finished intermediate product; the surface-finishing powder comprises a second binder and a glaze, and the first binder and the second binder independently comprise kaolin and / or argillaceous clay;
[0009] The surface-treated intermediate product is dried and calcined in sequence to obtain the surface-wear-resistant molecular sieve.
[0010] Preferably, the A-type molecular sieve raw powder is a potassium-based A-type molecular sieve raw powder, with a potassium ion exchange degree of 40-70%, a silicon-aluminum ratio of 1.9-2.1, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0011] Preferably, the silicon-to-aluminum ratio of the first binder and the second binder is independently 1.75 to 2.3, and the silicon-to-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0012] Preferably, the reinforcing agent comprises quartz glass fiber, the mass content of SiO2 in the quartz glass fiber is ≥99%, the fiber length is 70-120 μm, and the diameter is 2-4 μm.
[0013] Preferably, the mass of the first binder is 30-40% of the total mass of the type A molecular sieve powder and the first binder, and the mass of the enhancer is 5‰-15‰ of the total mass of the type A molecular sieve powder and the first binder. The masses of the first binder and the type A molecular sieve powder are both calculated on a dry basis.
[0014] Preferably, the intermediate product to be surface-finished has a water content of 31 to 42 wt % and a particle size of 1.5 to 5.0 mm.
[0015] Preferably, the glaze is a powdered inorganic silicate high-temperature calcined composition, the mass of the glaze is 40-60% of the total mass of the glaze and the second binder, and the second binder is calculated by dry weight; the applied amount of the surface finishing powder is 4-6% of the mass of the intermediate to be surface finished.
[0016] Preferably, the drying temperature is 80-180° C., and the holding time is 1-2 hours; the calcining temperature is 650-750° C., and the holding time is 60-180 minutes.
[0017] The present invention provides a surface wear-resistant molecular sieve prepared by the preparation method described in the above technical solution.
[0018] The present invention provides the use of the surface wear-resistant molecular sieve described in the above technical solution as an adsorbent in a refrigeration system.
[0019] The present invention provides a method for preparing a surface wear-resistant molecular sieve, comprising the following steps: mixing type A molecular sieve raw powder, a first binder, a reinforcing agent and water to form a mixture to obtain an intermediate product to be surface-finished; pre-wetting the surface of the intermediate product to be surface-finished and applying surface finishing powder to the surface, and curing to obtain a surface-finished intermediate product; drying and roasting the surface-finished intermediate product in sequence to obtain the surface wear-resistant molecular sieve. The preparation process of the present invention includes "mixing and forming", "surface finishing" and "drying and roasting"; wherein the reinforcing agent added in "mixing and forming" is combined with the glaze in "surface finishing" to make the adsorbent have a structure similar to a steel cage, so that the molecular sieve has excellent compressive resistance and a dense surface; the selection of the adhesive in "mixing and forming" and the "drying and roasting" process adopted make the molecular sieve have higher compressive resistance; the above two points make the molecular sieve have excellent wear resistance. At the same time, the "surface finishing" process forms a glossy surface similar to ceramics on the surface of the molecular sieve, which can make the molecular sieve have lower surface dust.
[0020] The present invention provides a surface wear-resistant molecular sieve prepared by the preparation method described in the above technical solution. The molecular sieve prepared by the present invention has excellent wear resistance and low surface dust. The static water adsorption capacity (25°C, RH75%) of the molecular sieve is greater than 18%, the surface dust is ≤40ppm, and the wet abrasion is ≤1.0%. DETAILED DESCRIPTION
[0021] The present invention provides a method for preparing a surface wear-resistant molecular sieve, comprising the following steps:
[0022] Mixing the A-type molecular sieve raw powder, the first binder, the reinforcing agent and water to form an intermediate product to be surface-finished;
[0023] Pre-wetting the surface of the intermediate product to be surface-finished and applying surface-finishing powder on the surface in sequence, and curing to obtain a surface-finished intermediate product; the surface-finishing powder comprises a second binder and a glaze, and the first binder and the second binder independently comprise kaolin and / or argillaceous clay;
[0024] The surface-treated intermediate product is dried and calcined in sequence to obtain the surface-wear-resistant molecular sieve.
[0025] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0026] The present invention mixes A-type molecular sieve raw powder, a first binder, a reinforcing agent and water to form an intermediate product to be surface-finished.
[0027] In the present invention, the A-type molecular sieve raw powder is preferably a potassium-based A-type molecular sieve raw powder, and the potassium ion exchange degree (in molar ratio: K + / (Na + +K + ) is preferably 40 to 70%, more preferably 45 to 55%, and the pore diameter of the molecular sieve is It has good compatibility with refrigerant. In the present invention, the silicon-aluminum ratio of the A-type molecular sieve raw powder is preferably 1.9-2.1, more preferably 1.95-2.05, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0028] In the present invention, the first binder comprises kaolin and / or kaolin, and the silicon-aluminum ratio of the first binder is preferably 1.75-2.3, more preferably 1.8-2.1, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0029] In the present invention, the reinforcing agent preferably comprises quartz glass fiber, the mass content of SiO2 in the quartz glass fiber is preferably ≥99%, the fiber length is preferably 70 to 120 μm, and the diameter is preferably 2 to 4 μm.
[0030] In the present invention, the mass of the first binder is preferably 30-40% of the total mass of the original powder of type A molecular sieve and the first binder, and can be 30%, 35%, 38% or 40%. The mass of the reinforcing agent is preferably 5‰-15‰ of the total mass of the original powder of type A molecular sieve and the first binder, more preferably 6‰-12‰, and further preferably 6‰-7‰. The masses of the first binder and the original powder of type A molecular sieve are both calculated on a dry basis. In the present invention, if the amount of the first binder added is too little, the molecular sieve has high static water adsorption, low crushing resistance, and high dry and wet abrasion; if the amount of the first binder added is too much, the molecular sieve has low static water adsorption and does not meet the standard.
[0031] In the present invention, the water is preferably deionized water.
[0032] In the present invention, the specific operation of the molding is preferably: mixing the A-type molecular sieve raw powder, the first binder and the reinforcing agent in a mixer to obtain a mixed powder, adding the mixed powder and water into the molding equipment to obtain the intermediate product to be surface-finished. In the present invention, the molding equipment is preferably a spherical equipment, that is, a spherical intermediate product to be surface-finished is obtained. In the present invention, the water content of the intermediate product to be surface-finished is preferably 31-42wt%, more preferably 31-35%, and the particle size is preferably 1.5-5.0mm (i.e. ), more preferably 1.5 to 2.5 mm.
[0033] After obtaining the intermediate product to be surface-finished, the present invention sequentially pre-wets the surface of the intermediate product to be surface-finished and applies surface-finishing powder on the surface, and obtains the surface-finished intermediate product after curing.
[0034] In the present invention, the intermediate product to be surface-modified is preferably added into a sugar coating machine, and water is sprayed into the machine in an atomized state while the machine is rotating to pre-wet the surface of the intermediate product to be surface-modified. In the present invention, the water is preferably deionized water, and the mass ratio of the water to the intermediate product to be surface-modified is preferably 1:70.
[0035] In the present invention, the surface finishing powder includes a second binder and a glaze, and is preferably mixed with the second binder and the glaze, and the mixing is preferably carried out in a mixer. In the present invention, the second binder is preferably the same as the first binder, and will not be repeated here. In the present invention, the glaze is preferably a powdered inorganic silicate high-temperature calcined composition. In the embodiment of the present invention, the glaze is purchased from Foshan Taoyise Glaze Co., Ltd., model G107; the mass of the glaze is preferably 40-60% of the total mass of the glaze and the second binder, more preferably 40-50%, and further preferably 45-50%, and the second binder is measured by dry weight. In the present invention, the amount of surface finishing powder applied is preferably 4-6% of the quality of the intermediate to be surface finished, more preferably 4.5-5.5%, and further preferably 4.5-5%.
[0036] In the present invention, the surface finishing powder is preferably sprinkled on the wet surface of the intermediate product to be surface finished after the surface is pre-wetted, and the sugar coating machine is continuously rotated to obtain the surface finished intermediate product after the surface is solidified.
[0037] After obtaining the surface-modified intermediate product, the present invention sequentially dries and calcines the surface-modified intermediate product to obtain the surface-wear-resistant molecular sieve.
[0038] In the present invention, the drying temperature is preferably 80 to 180° C., more preferably 120 to 150° C., and the heat preservation time is preferably 1 to 2 hours, more preferably 1 hour.
[0039] In the present invention, the calcination temperature is preferably 650-750°C, more preferably 680-720°C, further preferably 700-720°C, and the holding time is preferably 60-180min, more preferably 100-120min. During the calcination process, the glaze is melted to form a bright surface, and at the same time, a structure similar to a steel cage can be formed with the reinforcing agent. Because of the presence of a binder, a dense membrane with a channel can be formed, and the pores will not be blocked. In the present invention, the selected binder is composed of many layer structures tightly stacked together, and has higher compressive resistance after calcination. The calcination process used in the present invention can ensure that the surface finishing intermediate is fully calcined at high temperature without destroying the structure of the molecular sieve and the adhesive. In the present invention, if the calcination temperature is too low, the reinforcing agent in the molecular sieve and the glaze in the surface finishing powder cannot be effectively welded, resulting in a decrease in crushing resistance and high wet wear; if the calcination temperature is too high, the water absorption performance of the molecular sieve will decrease.
[0040] After the calcination is completed, the obtained product is preferably naturally cooled to room temperature in a dryer to obtain the surface wear-resistant molecular sieve.
[0041] The present invention provides a surface wear-resistant molecular sieve prepared by the preparation method described in the above technical solution. The molecular sieve provided by the present invention has excellent wear resistance and low surface dust, and is a high surface wear-resistant molecular sieve. The static water adsorption capacity (25°C, RH75%) of the molecular sieve is greater than 18%, the surface dust is ≤40ppm, the wet abrasion is ≤1.0%, and the particle size is 1.5-5.0mm.
[0042] The present invention provides the application of the surface wear-resistant molecular sieve described in the above technical solution as an adsorbent in a refrigeration system. The present invention has no special requirements for the application method, and the application method familiar to those skilled in the art can be used.
[0043] In order to further illustrate the present invention, the surface wear-resistant molecular sieve provided by the present invention and its preparation method and application are described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the present invention.
[0044] In each embodiment, the potassium ion exchange degree (molar ratio: K + / (Na + +K + )) is 45%, and the silicon-aluminum ratio (SiO2 / Al2O3) is 2.0; the silicon-aluminum ratio (SiO2 / Al2O3) of kaolin is 1.95; the SiO2 content of quartz glass fiber is ≥99%, the length is 70-120μm, and the diameter is 2-4μm; the glaze is a white powdery inorganic silicate high-temperature calcined synthetic material, purchased from Foshan Taoyise Glaze Co., Ltd., model G107.
[0045] Example 1
[0046] A high surface wear-resistant molecular sieve, the preparation method is as follows:
[0047] (1) Preparation of surface finishing powder: 10 kg of kaolin binder (accounting for 50% of the total weight (dry basis) of glaze and binder, with a water content of 20.2%) and 8 kg of glaze are mixed in a mixer to obtain surface finishing powder, which is then taken out for use.
[0048] (2) 50.2 kg of potassium-based type A molecular sieve raw powder (water content 20.3%), 30.5 kg of kaolin as a binder (water content 19.8%, accounting for 38% of the total weight (dry basis) of the potassium-based type A molecular sieve raw powder and the binder), and 0.42 kg of quartz glass fiber as a reinforcing agent were mixed in a mixer to obtain a mixed powder. The mixed powder was added to a ball-forming device while adding deionized water to obtain an intermediate product to be surface-finished with a diameter of 1.5 to 2.5 mm, and the water content was 31.5%.
[0049] (3) 21 kg of the intermediate product to be surface-treated is added to a sugar coating machine. While the machine is rotating, 0.3 kg of deionized water is sprayed into the machine in an atomized state to pre-wet the surface of the intermediate product to be surface-treated. Then, 1 kg of surface treatment powder is sprinkled on the wetted surface of the intermediate product to be surface-treated. The sugar coating machine is continuously rotated until the surface color is uniform and solidified to obtain the surface-treated intermediate product.
[0050] (4) The surface-treated intermediate product was dried at 150°C for 1 hour, calcined at 720°C for 2 hours, and cooled to room temperature in a dryer to obtain a highly wear-resistant molecular sieve.
[0051] Example 2
[0052] A high surface wear-resistant molecular sieve was prepared according to the method of Example 1, except that:
[0053] In step (2), the amount of kaolin as a binder added is 33.3 kg (water content 19.8%) (accounting for 40% of the total weight (dry basis) of the potassium-based A-type molecular sieve raw powder and the binder);
[0054] In step (4), the drying temperature of the surface-treated intermediate product is 120° C., and the constant-temperature roasting temperature is 680° C.;
[0055] The rest is the same as Example 1.
[0056] Example 3
[0057] A high surface wear-resistant molecular sieve was prepared according to the method of Example 1, except that:
[0058] In step (2), the amount of kaolin as a binder added is 26.8 kg (water content 19.8%) (accounting for 35% of the total weight (dry basis) of the potassium-based A-type molecular sieve raw powder and the binder);
[0059] In step (4), the drying temperature of the surface-treated intermediate product is 120° C., and the constant-temperature roasting temperature is 700° C.;
[0060] The rest is the same as Example 1.
[0061] Comparative Example 1
[0062] The molecular sieve was prepared according to the method of Example 1, except that:
[0063] The preparation of the surface finishing powder in step (1) and the surface finishing operation in step (3) are not performed;
[0064] The intermediate product to be surface-finished is directly processed according to the process requirements of step (4).
[0065] Comparative Example 2
[0066] The molecular sieve was prepared according to the method of Example 1, except that:
[0067] In step (2), the binder is changed to attapulgite, and the amount of attapulgite added is 30.3 kg (water content 19.3%, accounting for 38% of the total weight (dry basis) of the potassium-based A-type molecular sieve raw powder and the binder);
[0068] The rest is the same as Example 1.
[0069] Comparative Example 3
[0070] The molecular sieve was prepared according to the method of Example 1, except that:
[0071] Step (4) The surface-finished intermediate product is dried at 150° C. for 1 h and then calcined at 600° C. for 2 h;
[0072] The rest is the same as Example 1.
[0073] The molecular sieves prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance testing, including:
[0074] (1) The static water adsorption capacity (25°C, RH75%) of the prepared molecular sieve was analyzed using a constant temperature and humidity chamber;
[0075] (2) The prepared molecular sieve was subjected to wet abrasion analysis using a Red Devil wet abrasion tester (the sample was pretreated with saturated water before the measurement, and the test solvent was water);
[0076] (3) Dry attrition analysis of the prepared molecular sieve was performed using a KM-IV particle attrition tester;
[0077] (4) Using an intelligent particle strength tester to analyze the crushing resistance of the prepared molecular sieve;
[0078] (5) The surface dust of the prepared molecular sieve was analyzed using a WGZ-1 turbidity meter. The specific method was as follows: 5 ± 0.01 g of the sample was placed in 100 mL of deionized water and allowed to stand for 40 to 60 min to allow the dust in the sample to enter the liquid phase. The dust content was obtained by comparing the change in the transmittance of the liquid phase with that of the standard solution (surface dust was 0 ppm).
[0079] The above test results are shown in Table 1.
[0080] Table 1 Test results of molecular sieves prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0081]
[0082] It can be seen from the above examples that the molecular sieve prepared by the present invention has excellent wear resistance and low surface dust.
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a surface wear-resistant molecular sieve, characterized in that: The following steps are involved: Mixing the A-type molecular sieve raw powder, the first binder, the reinforcing agent and water to form an intermediate product to be surface-finished; Pre-wetting the surface of the intermediate product to be surface-finished and applying surface-finishing powder on the surface in sequence, and curing to obtain a surface-finished intermediate product; the surface-finishing powder comprises a second binder and a glaze, and the first binder and the second binder independently comprise kaolin and / or argillaceous clay; The surface-treated intermediate product is dried and calcined in sequence to obtain the surface-wear-resistant molecular sieve.
2. The preparation method according to claim 1, characterized in that: The A-type molecular sieve raw powder is a potassium-based A-type molecular sieve raw powder, with a potassium ion exchange degree of 40-70% and a silicon-aluminum ratio of 1.9-2.1, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
3. The preparation method according to claim 1, characterized in that: The silicon-to-aluminum ratio of the first binder and the second binder is independently 1.75 to 2.3, and the silicon-to-aluminum ratio is calculated as a molar ratio of SiO2 to Al2O3.
4. The preparation method according to claim 1, characterized in that: The reinforcing agent comprises quartz glass fiber, the mass content of SiO2 in the quartz glass fiber is ≥99%, the fiber length is 70-120 μm, and the diameter is 2-4 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass of the first binder is 30-40% of the total mass of the A-type molecular sieve powder and the first binder, and the mass of the enhancer is 5‰-15‰ of the total mass of the A-type molecular sieve powder and the first binder. The masses of the first binder and the A-type molecular sieve powder are both calculated on a dry basis.
6. The preparation method according to claim 1, characterized in that: The intermediate product to be surface-finished has a water content of 31-42 wt % and a particle size of 1.5-5.0 mm.
7. The preparation method according to claim 1, characterized in that: The glaze is a powdered inorganic silicate high-temperature calcined composition, the mass of the glaze is 40-60% of the total mass of the glaze and the second binder, and the second binder is calculated by dry weight; the applied amount of the surface finishing powder is 4-6% of the mass of the intermediate to be surface finished.
8. The preparation method according to claim 1, characterized in that: The drying temperature is 80-180° C., and the heat preservation time is 1-2 hours; the calcination temperature is 650-750° C., and the heat preservation time is 60-180 minutes.
9. The surface wear-resistant molecular sieve prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the surface wear-resistant molecular sieve according to claim 9 as an adsorbent in a refrigeration system.